Karakteristik Tanah Pada Lereng Sebagai Mitigasi Pasca Bencana Tanah Longsor (Studi Kasus: Nagari Aie Dingin, Kab. Solok, Sumatera Barat) - Ayunimas, Agustina; Haryati, Novy; Sonata, Herix; Muchlian, Meli (Jurnal Bangunan, Konstruksi & Desain, 2023)
The landslide disaster in the Nagari Aia Winter area, Lembah Gumanti District, Solok Regency, which was caused by high-intensity rain and other factors, is thought to be due to mining activities in the area which caused the contour of the land there to become unstable. This research aims to analyze the soil characteristic values on the slopes, analyze the Safety Factor (FK) values of the slopes and analyze appropriate mitigation for landslide disasters in Nagari Aia Winter, Lembah Gumanti District. The research method used is a quantitative approach. From the results of the research carried out, it can be concluded that the characteristics of the soil on the slope include a type of silty sand soil with poor gradation and calculations using the Geostudio Slope/W 2012 program show the Safety Factor (FK) value of the slope in Nagari Aia Winter, Lembah Gumanti District, Solok Regency by simulating using angles of 30°, 45°, 60°, 70°, it was found that the Safety Factor (FK) value < 1.5, the slope was included in an unstable condition. These slopes are dangerous and can cause landslides in the future. Mitigation efforts that can be carried out are structural mitigation by building retaining walls or stone slabs and drainage at landslide locations, mapping slopes or sloping steep slopes and making permanent connecting bridges. Non-structural mitigation can take the form of providing information related to landslide-prone zones, and conducting outreach at several locations that have landslide-prone impacts.